Competing, cooperating, deciding: towards a model of deliberative debate - CATTANI, ADELINO; Mastroianni, Bruno (Communication and Philosophical Cultures. Researches and Instruments, 2021)
Will there be any 'happy dispute' again? A debate among people holding different opinions that does not end with a repetition of the initial idea, but rather with an improvement of one's own beliefs and those of others? In order to achieve this, we need to rely on education which, through deliberative debate training activities, can foster the development of rhetorical and dialectical skills (the ability to persuade and compete) as well as critical thinking and open-mindedness (living together and cooperating). A number of scholars from around the world reflect on the topic both from a theoretical point of view - the significance of debate in a hyperconnected society - and from a practical point of view, the application of educational models and tools to measure their effectiveness.